Descentralização ou desconcentração : AIS-SUDS-SUS - Berenger, Mercedes Moreira (1996)
The current centralization process on the health area has ocurred by means of a strong deconcentration mechanism. The analysis of the three pro posais for the reorganization of the health area, within the period 1983-1990, aims at a change of strategy in the deconcentration mechanism. Previously, the central institutions kept deconcentrated structures acting over intermediate and local leveis. As from 1983, the trend is to observe intermediate and local leveis operating as deconcentrated structures. Therefore, deconcentration is in fact ocurring in the health area. Deconcentration may have two different aims, i.e., it can be a strengthening and updating strategy for centralization or it can be a strengthening strategy at intermediate and local leveis, and, therefore, a tool to facilitate and promote decentralization. Taking into consideration the historical development of the health area in Brazil, it would be necessary to investigate the present purpose of deconcentration.